Exogenous Cysteine Improves Mercury Uptake and Tolerance in Arabidopsis by Regulating the Expression of Heavy Metal Chelators and Antioxidative Enzymes - Kim, Yeon-Ok; Gwon, Yonghyun; Kim, Jangho (Frontiers in Plant Science, 2022)
Cysteine (Cys) is an essential amino acid component of the major heavy metal chelators, such as glutathione (GSH), metallothioneins (MTs), and phytochelatins (PCs), which are involved in the pathways of mercury (Hg) tolerance in plants. However, the mechanism through which Cys facilitates Hg tolerance in plants remains largely unclear. In this study, we investigated the effects of exogenous Cys on Hg uptake in the seedlings, roots, and shoots of Arabidopsis throughout 6 and 36 h of Hg exposure and on the regulation of Hg detoxification by heavy metal chelators and antioxidative enzymes. The results showed that exogenous Cys significantly improved Hg tolerance during the germination and seedling growth stages in Arabidopsis, cabbage, Camelina, lettuce, and radish. Exogenous Cys significantly promoted Hg uptake in Arabidopsis roots by upregulating the expression of the Cys transporter gene AtLHT1, resulting in increased Hg accumulation in the roots and seedlings. In Arabidopsis seedlings, exogenous Cys further increased the Hg-induced glutathione synthase (GS1 and GS2) transcript levels, and the Hg and Hg+Cys treatments greatly upregulated MT3 expression after 36 h exposure. In the roots, MT3 was also significantly upregulated by treatment of 36 h of Hg or Hg+Cys. Notably, in the shoots, MT2a expression was rapidly induced (10-fold) in Hg presence and further markedly increased (20-fold) by exogenous Cys. Moreover, in the seedlings, exogenous Cys upregulated the transcripts of all superoxide dismutase (CuSOD1, CuSOD2, MnSOD1, FeSOD1, FeSOD2, and FeSOD3) within 6 h and subsequently increased the Hg-induced GR1 and GR2 transcript levels at 36 h, all of which could eliminate the promotion of reactive oxygen species production and cell damage caused by Hg. Additionally, exogenous Cys upregulated all the antioxidative genes rapidly in the roots and subsequently increased the expression of CuSOD1, CuSOD2, and MnSOD1 in the shoots. These results indicate that exogenous Cys regulates the transcript levels of heavy metal chelators and antioxidative enzymes differently in a time- and organ-specific manner under Hg stress. Our study elucidates the positive functional roles of exogenous Cys in the Hg uptake and tolerance mechanisms of plants and provides a novel strategy for the phytoremediation of Hg-contaminated soils.